The Influence of Industrial Relations and Communication on the Effectiveness of Village Office Employees Post the Covid-19 Pandemic - Yuliana, Yuliana; AR, Hasmawaty (SEIKO : Journal of Management & Business, 2023)
This study aims to analyze the impact of industrial relations and communication on employee effectiveness at the Batun Baru Village Office. In a modern work environment, employee effectiveness plays an important role in achieving organizational goals. Batun Baru Village Office, as a government entity that supports local communities, is also not exempt from challenges related to employee effectiveness. The research method used was quantitative, involving 76 employees as the research sample. The necessary data was collected using questionnaires. Data analysis was then conducted to understand the extent to which industrial relations and communication influence employee effectiveness at Batun Baru Village Office. The results of this study show that there is a significant influence between industrial relations and communication on employee effectiveness at the Batun Baru Village Office. In other words, the better the industrial relations and communication in the work environment, the higher the level of effectiveness that employees can achieve in carrying out their tasks. The implication of this research is the importance of strengthening industrial relations and communication in improving employee effectiveness in the village office environment. Therefore, management at Batun Baru Village Office should pay attention to these aspects and develop strategies to improve industrial relations and communication to create a more efficient and productive work environment.